1990
DOI: 10.1007/bf00966217
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol alters astrocyte development: A study of critical periods using primary cultures

Abstract: Using astrocytes obtained from 21-day-old rat fetuses, in primary culture, we have analyzed the effect of prenatal alcohol consumption on DNA and protein synthesis of astrocytes during their development. The variation in sensitivity of astrocytes to ethanol "in vitro" during the proliferation and maturation periods was also assessed. Control astrocytes showed peaks of DNA and protein synthesis at 8 and 15 days, respectively. A significant decrease in both DNA and protein synthesis was found in astrocytes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 22 publications
6
53
0
Order By: Relevance
“…Ethanol has been shown to inhibit basal astroglial proliferation and response to mitogenic factors such as IGF-1 and acetylcholine (35,47 (49). High concentrations of ethanol alter cell-cycle kinetics of proliferating astrocytes by delaying the passage of the cells trough G1 (49). These effects appear to be dosedependent.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Ethanol has been shown to inhibit basal astroglial proliferation and response to mitogenic factors such as IGF-1 and acetylcholine (35,47 (49). High concentrations of ethanol alter cell-cycle kinetics of proliferating astrocytes by delaying the passage of the cells trough G1 (49). These effects appear to be dosedependent.…”
Section: Discussionmentioning
confidence: 90%
“…Proliferation of astrocytes is mainly controlled by soluble mitogenic factors such as growth factors acting on tyrosine kinase-coupled receptors (45,46). Ethanol has been shown to inhibit basal astroglial proliferation and response to mitogenic factors such as IGF-1 and acetylcholine (35,47 (49). High concentrations of ethanol alter cell-cycle kinetics of proliferating astrocytes by delaying the passage of the cells trough G1 (49).…”
Section: Discussionmentioning
confidence: 99%
“…Functional alterations in related circuits, including the central amygdala, frontal cortex, NAc, and bed nucleus of the stria terminalis (BNST) have been vigorously examined, and several molecular mechanisms have been implicated in the transition from acute to chronic alcohol consumption, including corticotropin-releasing factor (CRF), neuropeptide Y (NPY), and endogenous opioids (Mitchell et Although alcohol-induced effects on glia have not been as extensively characterized as its effects on neurons, accumulating evidence suggests that both microglia and astrocytes are impacted by acute and chronic alcohol. Early in vitro work with astrocyte progenitors cultured from fetal rat brains found that acute alcohol resulted in reduced GFAP expression in addition to stunted astrocyte cell proliferation (Guerri et al, 1990;Renau-Piqueras et al, 1989). In vivo, rats given free access to alcohol show increased activation of astrocytes (measured by GFAP) in discrete subregions of the hippocampus following shorter exposure periods (4-12 weeks), but decreased astrocyte activation was observed following extended drug access (36 weeks) (Franke, 1995).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 99%
“…The potential number of cycles depends on the length of the cell cycle and the number of days (or hours) during which neurons are generated. In the cerebral cortex (Miller, 1986;1988;Siegenthaler and Miller, 2005) and in primary cultures of astrocytes (Guerri et al, 1990;Luo and Miller 1999) or neurons (Jacobs and Miller, 2001), ethanol increases the length of the cell cycle. On the other hand, at least in the PSN (Miller and Muller, 1989), ethanol does not increase the period of neuronal generation.…”
Section: Mechanisms Of Ethanol Toxicitymentioning
confidence: 99%